Novel device for dividing core needle biopsy specimens to provide paired mirror image-like tissues for genetic and pathological tests - Yuichi Nakamura; Keisuke Tsuji; Takumi Shiraishi; Satoshi Sako; Ryota Ogura; Hideto Taga; Yuta Inoue; Munehiro Ohashi; Saya Ueda; Takeshi Yamada; Takashi Ueda; Atsuko Fujihara; et al. (Scientific Reports, 2023)
Abstract In a world that seeks precision medicine, genetic testing is gaining importance in clinical decision making. We previously reported the utility of a novel tool for longitudinally dividing core needle biopsy (CNB) tissues into two filamentous tissues that can provide paired mirror image-like tissues (mirror-tissues) that spatially match each other. In this study, we investigated its application in gene panel testing in patients who underwent prostate CNB. Four hundred and forty-three biopsy cores were obtained from 40 patients. Of them, 361 biopsy cores (81.5%) were judged by a physician to be appropriate for dividing into two pieces using the new device, of which a histopathological diagnosis was successfully reached in 358 biopsy cores (99.2%). Among them, the quality and quantity of nucleic acid in 16 appropriately divided cores were assessed and found to be sufficient for gene panel testing, and histopathological diagnosis was successfully obtained from the remaining divided cores. The novel device for longitudinally-dividing CNB tissue provided mirror image-like paired-tissues for gene panel and pathology testing. The device might be a promising tool for obtaining genetic and molecular biological information, in addition to histopathological diagnosis, helping to advance personalized medicine.